The relationship of personality traits and work attitudes to job satisfaction - Laguyo, Delia D. 1957-
The research aimed to verify some of the theories and findings with regards to the relationship of personality traits and work attitude variables to job satisfaction. Specifically, it aimed to determine if there is a significant relationship between scores of personality traits and work attitude variables and also if there is a positive relationship between job satisfaction with personality traits and work attitude variables.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Job satisfaction; Personality